2013
DOI: 10.1111/1756-185x.12221
|View full text |Cite
|
Sign up to set email alerts
|

Meta-analysis of association between cytokine gene polymorphisms and Behcet's disease risk

Abstract: The aim of this study was to perform a meta-analysis of eligible studies to derive precise estimation of the association of interleukin-1 (IL-1), IL-10 and tumor necrosis factor (TNF)-a polymorphisms with Behcet's disease (BD). Odds ratios (ORs) and 95% confidence intervals (CIs) were used to assess the strength of the association. A total of 4003 cases and 4748 controls in 19 eligible studies were included in the meta-analysis. We examined the relationship between seven single nucleotide polymorphisms (SNPs) … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
28
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 21 publications
(28 citation statements)
references
References 33 publications
0
28
0
Order By: Relevance
“…The data suggest significant evidence for publication bias in two comparisons (p=0.016 for IL-1R2 rs2310173 and p=0.035 for IL-23R rs7517847). Therefore, we used the ‘trim and fill’ method to adjust summary estimates for observed bias 26. The adjusted pooled OR and its 95% CI indicated no significant difference between the unadjusted and adjusted results, which indicated that the result of the meta-analysis was not changed due to publication bias.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The data suggest significant evidence for publication bias in two comparisons (p=0.016 for IL-1R2 rs2310173 and p=0.035 for IL-23R rs7517847). Therefore, we used the ‘trim and fill’ method to adjust summary estimates for observed bias 26. The adjusted pooled OR and its 95% CI indicated no significant difference between the unadjusted and adjusted results, which indicated that the result of the meta-analysis was not changed due to publication bias.…”
Section: Resultsmentioning
confidence: 99%
“…Therefore, the meta-analysis can be a useful method for summarising the association between the gene polymorphisms with the diseases 26. In this study, we investigated the abovementioned cytokine gene polymorphisms and the pathogenesis of AS.…”
Section: Introductionmentioning
confidence: 99%
“…In fact, the TNF-α regulatory regions may play a role in cytokine production, and the binding of inducible cytoplasmatic factors may result in the translational blockade, leading to the dysregulated cytokine production. Genotype-phenotype correlation studies reported that G allele conferred two-fold lower effects on the transcription level than A allele [8][9][10][11][12][13][14][15][16][17][18][19][20][21]26].…”
Section: Genotyping Ofmentioning
confidence: 99%
“…The polymorphism was previously associated with increased susceptibility to and severity of rheumatoid arthritis, psoriatic arthritis, ankylosing spondylitis, inflammatory bowel disease, vitiligo, multiple sclerosis, cardiomyopathy and malignancies, as well as of pre-eclampsia and celiac disease. It was reported that patients with the AA genotype and inflammatory diseases who are treated with anti-TNFα therapies may be less likely to have improvement in symptoms as compared to patients with the GG genotype [8][9][10][11][12][13][14][15][16][17][18][19][20][21]. TNFα -308A…”
Section: Introductionmentioning
confidence: 99%
“…In addition to the well‐established human leukoctye antigen ( HLA ) locus, common polymorphisms in interleukin ( IL23R–IL12RB2 ) and IL10 have been recently associated with BD in two independent GWAS in Turkish and Japanese datasets and replicated in an Iranian sample and in a recent meta‐analysis . IL10 has a central role in the suppression of inflammatory cytokines inhibiting the costimulatory activity of macrophages for T‐cell and natural killer (NK)‐cell activation.…”
Section: Introductionmentioning
confidence: 99%